Molecular Dynamics Simulations to Determine the Neuroprotective Mechanisms of Curcumin - Stone, William (URJ-UCCS: Undergraduate Research Journal at UCCS, 2020)
Since 1992, Amyloid Beta protein has been investigated as the causative agent in Alzheimer's Disease due to its neurotoxic effects on cell membranes. Curcumin is a polyphenol found in turmeric and has been demonstrated to have neuroprotective effects against Amyloid Beta. In order to investigate the chemical mechanisms of this protection, atomistic molecular dynamics (MD) simulations were designed to model Amyloid Beta interactions with a model lipid membrane. In a parallel system, curcumin was embedded into the lipid membrane and simulations were performed to determine how the polyphenol alters Amyloid Beta interactions with the membrane. Visual inspection of coordinate files and RMSD calculations revealed that the curcumin alters the trajectory of the protein and bilayer thickness calculations showed that the membrane is thicker in the presence of curcumin.